2022
DOI: 10.3389/fnut.2022.995295
|View full text |Cite
|
Sign up to set email alerts
|

Global leaders malnutrition initiative-defined malnutrition affects long-term survival of different subgroups of patients with gastric cancer: A propensity score-matched analysis

Abstract: As defined by the Global Leaders Malnutrition Initiative (GLIM), malnutrition is strongly associated with a lower quality of life and poor prognosis in gastric cancer patients. However, few studies have precisely explored the predictors of malnutrition, as defined by the GLIM, for overall survival (OS) after gastric cancer surgery in subgroups of patients stratified according to population characteristics. Our research aimed to analyze whether the predictors of malnutrition defined by the GLIM for postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The causes of malnutrition in patients with gastric cancer with pyloric stenosis were multiple, mainly related to feeding difficulties and disease progression ( 26 30 ). The present study indicated that patients with pyloric stenosis were more prone to abdominal distension and higher TNM stage, which were the main reasons for malnutrition and shorter survival ( 31 34 ). The NRI contains ALB levels and body weight, which are closely related to the prognosis of patients with gastric cancer ( 35 37 ).…”
Section: Discussionmentioning
confidence: 61%
“…The causes of malnutrition in patients with gastric cancer with pyloric stenosis were multiple, mainly related to feeding difficulties and disease progression ( 26 30 ). The present study indicated that patients with pyloric stenosis were more prone to abdominal distension and higher TNM stage, which were the main reasons for malnutrition and shorter survival ( 31 34 ). The NRI contains ALB levels and body weight, which are closely related to the prognosis of patients with gastric cancer ( 35 37 ).…”
Section: Discussionmentioning
confidence: 61%
“…Univariate and multivariate COX regression analyses revealed that GLIM-malnutrition (OR: 2.144, 95% CI: 1.234–3.728, P=0.007) was an independent risk factor for OS in older CRC patients. Likewise, GLIM-malnutrition was reported to be an independent risk factor for OS in patients with gastric cancer ( 25 ). Orell et al pointed out that among head and neck cancer patients, patients with GLIM-malnutrition had a shorter median survival time than well-nourished patients (57 vs. 72 months) ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low muscle mass is strongly correlated with malnutrition and should be taken into consideration when evaluating the nutritional status of patients with GC and GEJC [38]. The presence of sarcopenia can lead to poor long-term prognoses for patients undergoing surgery for upper GC [14][15][16][17][38][39][40][41]. Therefore, gaining an understanding of patients' dietary intake, factors affecting the ability to eat and/or absorb nutrients, reduced muscle mass, and muscle function are important considerations in addition to weight loss.…”
Section: Screening and Rd Referralmentioning
confidence: 99%